STUDI TENTANG KEMAMPUAN LITERASI INFORMASI DI KALANGAN SISWA MENENGAH PERTAMA - Rachmawati, Tine Silvana; -, Fitriawati; Saepudin, Encang (Edulib, 2017)
The research was conducted to the students of Al-Kausar Internat Junior high school as an example of school which has applied the concept of information literacy in one subject and Arrahman Junior high school as an example of school which has not applied the concept of information literacy yet. The aim of this research was to find out whether there is a significant differences between students' literacy ability in finishing task exercises from those school. The method used in this research was a descriptive comparative method to find out the differences between both of objects in this research. The data were collected through questionnaire, interviews, and library study. The respondents are 53 students selected through Proportionate stratified random sampling techniques. The findings show there is no significant differences between students of Alkautsar junior high school and Ar Rahman junior high school on their students' information literacy ability. However, from the output scores of mean view, Al Kautsar Junior high school has a larger score than Ar Rahman junior high school. Therefore, Alkautsar Junior high school students have a better information literacy ability compared to Ar Rahman Junior high school students.